ChemInform Abstract: Iridium‐Catalyzed Enantioselective Allylic Alkynylation. Issue 48 (26th November 2013) - Hamilton, James Y.; Sarlah, David; Carreira, Erick M.
Abstract This method allows the highly enantioselective substitution of racemic allylic alcohols with potassium alkynyltrifluoroborates with excellent branched‐to‐linear selectivity.